HISTOPATOLOGI ARTERI KORONER Rattus novergicus STRAIN WISTAR JANTAN PADA MINGGU KE-12 SETELAH PEMBERIAN DIET ATEROGENIK - Anwar Syaputra; Enikarmila Asni; Zulkifli Malik (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAtherosclerosis is a chronic inflammatory disease caused by endothelial dysfunction. Atherosclerosis can be induced in Rattus novergicus by feeding atherogenic diet and giving induction vitamin D3 to make the process of atherosclerosis happens earlier. The aim of this research is to know the difference of histopathologic atherosclerosis lesions of coronary artery of Rattus novergicus strain Wistar after being fed with atherogenic diet and standard diet after 12 weeks. This is an experimental laboratory research with post test only design. Twelve male rats were segregated into two groups (n=6) labelled as control fed standard diet and fed atherogenic diet (cholesterol 2% from yolk, goat fat 5% and cholic acid 0,2%) and induction of vitamin D3. The parameter which an analysis were score of atherosclerosis lesions. The result of atherosclerosis lesions of atherogenic group was found of all samples (100%) and of control group was found of four samples (66,67%). The statistic test result shows p=0,031. As the conclusion, the result shows significant difference of atherosclerosis lesions between atherogenic group and control group.Keywords: atherosclerosis, coronary artery, atherogenic diet, histopathology.